2021
DOI: 10.1017/s0007485321000419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the development and reproduction of Cinara cedri (Hemiptera: Aphidoidea: Lachninae)

Abstract: Temperature is one of the main factors affecting insect growth, development and reproduction. The effects of temperatures (10, 15, 20, 25 and 30°C) on the development and reproduction of Cinara cedri Mimeur (Hemiptera: Aphidoidea: Lachnidae) fed on Cedrus deodara (Roxb.) G. Don were evaluated in this study. With the increase of temperature from 10 to 30°C, the development duration at different development stages gradually shortened. There was a significant positive correlation between the developmental rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Information on food resources of cavity‐nesting bees and wasps also has the potential to provide new insight into their feeding ecology and to identify potential biocontrol species. For example, in the nests of P. fuscipennis and P. lugens , we found Aphis fabae , known as a major pest of beans, beets, or potatoes (Blackman & Eastop, 2000), and Cinara cedri , a known pest of diverse Cedrus species (Ji et al, 2021). For a complete list of host plants and their known economic importance, see Table S4.…”
Section: Discussionmentioning
confidence: 99%
“…Information on food resources of cavity‐nesting bees and wasps also has the potential to provide new insight into their feeding ecology and to identify potential biocontrol species. For example, in the nests of P. fuscipennis and P. lugens , we found Aphis fabae , known as a major pest of beans, beets, or potatoes (Blackman & Eastop, 2000), and Cinara cedri , a known pest of diverse Cedrus species (Ji et al, 2021). For a complete list of host plants and their known economic importance, see Table S4.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, they produce oviparae and males in October-November to produce egg to ensure to survive under the harsh conditions, and then following the overwintering egg individuals hatch around middle March-April on the same host plant(Blackman and Eastop, 2022; URL 5). Recent studies clearly indicated how temperature changes dramatically influence the life history traits of the C. cedri(Ji et al, 2021). The detected C. cedri population in Niğde Province clearly demonstrated how increased average temperature extended the parthenogenetic reproduction period of the population on the Cedrus sp.…”
mentioning
confidence: 91%
“…Foxglove aphid ( Aulacorthum solani ) reduces soybean yield by spreading viruses and sucking in leaf sap directly [ 7 ]. Cinara cedri feeds on cedar branches, secretes a large amount of honeydew, and pollutes the lower branches [ 8 ]. Daktulphophora vitifoliae (Fitch) mainly sucks the juice of grapes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%